Isozyme variation in natural populations of cork-oak (Quercus suber L) - Population structure, diversity, differentiation and gene flow - ElenaRossello, J A; Cabrera, E (SILVAE GENETICA, 1996)
Genetic variation of cork-oak (Quercus suber L.) was investigated in 7 Mediterranean populations in Spain using 13 loci from 7 enzyme systems. Quercus suber was found to possess higher values of heterozygosity (H = 0.288 +/- 0.069), percent of polymorphic loci at the 99% criterion (P = 76.9%) and average number of alleles per locus (A = 2.46), than any other oak species. Interpopulation diversity was about 16.9% of the total diversity. The average estimated of Nm based on 10 loci is 2.57, and shows current or recent gene now among populations. Genetic identities among populations were moderate, ranging from I = 0.829 to I = 0.999, and a cluster analysis revealed no patterns related to geography. Our results revealed that the Q. suber populations studied share a common gene pool. The number of alleles and genotypes and the levels of genetic variability in the study populations, indicate that the Spanish populations are genetically rich. These high levels of genetic variability, coupled with the ecological and economic importance of the species make Q. suber a strong candidate for a gene conservation program.
Keywords: gene diversity; gene flow; genetic differentiation; genetic identities; isozymes; population structure; Quercus suber

Isozyme variation in natural populations of cork-oak (Quercus suber L) - Population structure, diversity, differentiation and gene flow - ElenaRossello, J. A.; Cabrera, E. (SILVAE GENETICA, 1996)
Genetic variation of cork-oak (Quercus suber L.) was investigated in 7 Mediterranean populations in Spain using 13 loci from 7 enzyme systems. Quercus suber was found to possess higher values of heterozygosity (H = 0.288 +/- 0.069), percent of polymorphic loci at the 99% criterion (P = 76.9%) and average number of alleles per locus (A = 2.46), than any other oak species. Interpopulation diversity was about 16.9% of the total diversity. The average estimated of Nm based on 10 loci is 2.57, and shows current or recent gene now among populations. Genetic identities among populations were moderate, ranging from I = 0.829 to I = 0.999, and a cluster analysis revealed no patterns related to geography. Our results revealed that the Q. suber populations studied share a common gene pool. The number of alleles and genotypes and the levels of genetic variability in the study populations, indicate that the Spanish populations are genetically rich. These high levels of genetic variability, coupled with the ecological and economic importance of the species make Q. suber a strong candidate for a gene conservation program.
The following values have no corresponding Zotero field: pub-location: FINKENHOFSTRASSE 21, W-6000 FRANKFURT, GERMANY publisher: SAUERLANDERS VERLAG
Keywords: gene diversity; gene flow; genetic differentiation; genetic identities; isozymes; population structure; Quercus suber

PRELIMINARY DATA ON THE ECOLOGY OF WOODMOUSE APODEMUS-SYLVATICUS LINNE, 1758, NEAR TALA-GUILEF, DJURDJURA-NATIONAL-PARK ALGERIA - HAMDINE, W; POITEVIN, F (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1994)
Wood mice (n = 166) were sampled in 1989-1990 by line trapping in the Djurdjura National Park, Algeria. Most were observed in forests of sclerophyllous oaks (Quercus ilex, Quercus suber) and in mountain grasslands. The species was scarcer in cedar forests. Most (70 %) of the captured individuals were adults with a large number of males. Furthermore, most of the individuals were captured in spring (ca. 52 %).
Keywords: Algeria; Apodemus sylvaticus; Ecological abundance; Plant cover; population structure; seasonal variation; Sex ratio